Personal Characteristics and Cognition in Older African-Americans with Hypertension - Klymko, Kay W. (2011)
Hypertension disproportionately affects all African-Americans and lack of adequate blood pressure control could contribute to cognitive decline among older adult African-Americans. Cognitive difficulties might impair the self-management ability of these individuals, further limiting their blood pressure control. The purpose of this study, therefore, was to determine the personal characteristics that were associated with cognitive difficulties in order to identify older adults who needed environmental supports to enhance their self-management capabilities. A sample of 102 African-Americans from 60 to 89 years of age with diagnosed hypertension was recruited. Forty-nine percent (n = 50) of the sample had cognitive impairments that could hinder hypertension self-management. Depressive symptoms were also associated with a decrease in cognitive function (i.e., orientation and complex cognitive skills), as well as being negatively associated with social support. These findings support the need for nurses to assess personal characteristics in order to plan self-management strategies that help clients compensate for cognitive deficits.